1993
DOI: 10.2307/1592032
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Circulating Antibody and Cellular Immunity with Resistance against Cryptosporidium baileyi in Broiler Chickens

Abstract: The correlation of circulating antibody and cell-mediated immunity (CMI) with resistance to Cryptosporidium baileyi was studied using hormonal and chemical bursectomy in the one experiment and cyclosporin A in a second experiment. In Expt. 1, there was no correlation between antibody (confirmed by enzyme-linked immunosorbent assay) and resistance to infection as measured by body weight, gross lesions, morbidity, and mortality. Bursectomy altered antibody production, but not CMI, as measured by the delayed-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…The significance of these findings, and the reasons for exacerbation in the infected groups are not known. Other workers using CsA-treated chickens have not reported such signs (Hill et al, 1989;Corrier et al, 1991;Kogut & Eirmann, 1991;Hatkin et al, 1993;Dhinakar Raj & Jones, 1997), but the treatment has either not been as prolonged as here or the doses of CsA used were less.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…The significance of these findings, and the reasons for exacerbation in the infected groups are not known. Other workers using CsA-treated chickens have not reported such signs (Hill et al, 1989;Corrier et al, 1991;Kogut & Eirmann, 1991;Hatkin et al, 1993;Dhinakar Raj & Jones, 1997), but the treatment has either not been as prolonged as here or the doses of CsA used were less.…”
Section: Discussionmentioning
confidence: 47%
“…These include reovirus (Hill et al, 1989), coccidia (Kogut & Eirmann, 1991), salmonella (Corrier et al, 1991), Cryptosporidium baileyi (Hatkin et al, 1993), turkey haemorrhagic enteritis virus (Suresh & Sharma, 1995), marble spleen disease virus in pheasants (Fitzgerald et al, 1995), infectious bronchitis virus (Bhattacharjee et al, 1995;Dhinakar Raj & Jones, 1997), pneumovirus (Khehra & Jones, 1999), Leucocytozoon caulleryi (Isobe et al, 2000), infectious bursal disease (Bhawna Poonia & Shiv Charan, 2001), and turkey coronavirus (Loa et al, 2002). It has been reported that CsA prevents the synthesis of cytokines by T cells by blocking a latestage signalling pathway initiated by the T-cell receptor, which affects the production of IL-2; hence, T-cell proliferation is affected (Hill et al, 1989;Schreiber & Crabtree, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies have been demonstrated in sera from infected mammals infected with Cryptosporidium parvum; however, there is a lack of evidence for a protective role of serum antibodies in contrast with CMI (reviewed by Heyworth 1992). There is only one documented study dealing with the role of CMI and AMM in the immune response to C. baileyi in chickens (Hatkin et al 1993). In that study, hormonally bursectomized (B-lymphocyte-deficient), cyclosporin A-treated (T-lymphocyte-deficient), Table 1 Comparisons of the mean body weight, the relative weight of the bursa of Fabricius and thymus, the BSA antibody titers, the cutaneous PHA response, the total oocyst output, and the patency of IB, IT, and IC chickens inoculated orally with Crypto-sporidium baileyi oocysts.…”
Section: Resultsmentioning
confidence: 99%
“…Chickens acquire an immune response of sufficient magnitude to clear the parasite from the mucosa of the intestinal and respiratory tract and to make birds resistant to reinfection (Current and Snyder 1988;Sréter et al 1995). It has been suggested that cell-mediated mechanisms are more important in the acquired immune response to C. baileyi than are circulating antibodies in intratracheally infected broiler chickens (Hatkin et al 1993). The aim of the present study was to examine the correlation of antibody-and cell-mediated immunity with the resistance to C. baileyi in orally infected chickens.…”
Section: Introductionmentioning
confidence: 99%
“…2) and the lowest cellular (Fig. 5) response, con®rming the pivotal role of cellular immunity in expulsion of and resistance to C. baileyi (Hatkin et al 1993). Similarly, a single larger dose of oocysts was able to induce a stronger cellular response to OCA in group CB-1 than the continuous low level uptake in CB-tr (Fig.…”
Section: Discussionmentioning
confidence: 69%